Pemikiran Teologi Islam Nusantara: Analisis Hermeneutika Terhadap Pemikiran KH. Ali Maksum dalam Kitab Hujjah Ahlisunnah wal Jamaah - Farhan, Ibnu (Mahad Aly Al Fithrah, 2025)
Islamic theology, also known as ‘Ilm al-Kalām, ' constitutes a fundamental branch of Islamic sciences. Although traditionally classified as a classical discipline, its discourses continue to evolve in response to contemporary developments. This study aims to examine the theological thought of KH. Ali Maksum, a prominent Indonesian Muslim scholar, as presented in his work Hujjah Ahlisunnah wal Jamaah, and to analyze it through a hermeneutical lens. Employing a qualitative methodology with a library research approach, this study primarily utilizes Hujjah Ahlisunnah wal Jamaah as its primary source. The data is analyzed using Friedrich Schleiermacher’s hermeneutic theory. The findings reveal that KH. Ali Maksum represents a Nusantara scholar with original contributions to Islamic theology. The hermeneutical analysis indicates that Hujjah Ahlisunnah wal Jamaah was composed as a defence of religious practices upheld by Sunni Muslims, particularly those affiliated with the Nahdlatul Ulama organization. In this work, KH. Ali Maksum expands theological discourse beyond doctrinal matters (ʿaqīdah) to include jurisprudence (fiqh) and mysticism (taṣawwuf). The text serves as an intellectual and religious response from KH. Ali Maksum, as a pesantren leader and Rais ‘Aam of PBNU, affirms the continuity and legitimacy of the Ahlusunnah wal Jamaah tradition embraced by most Indonesian Muslims.